2008
DOI: 10.1016/j.neuron.2008.06.027
|View full text |Cite
|
Sign up to set email alerts
|

FMRP Acts as a Key Messenger for Dopamine Modulation in the Forebrain

Abstract: The fragile X mental retardation protein (FMRP) is an RNA-binding protein that controls translational efficiency and regulates synaptic plasticity. Here, we report that FMRP is involved in dopamine (DA) modulation of synaptic potentiation. AMPA glutamate receptor subtype 1 (GluR1) surface expression and phosphorylation in response to D1 receptor stimulation were reduced in cultured Fmr1(-/-) prefrontal cortex (PFC) neurons. Furthermore, D1 receptor signaling was impaired, accompanied by D1 receptor hyperphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(217 citation statements)
references
References 66 publications
9
206
2
Order By: Relevance
“…In studies of FMR1 mutant mice, Zhuo and colleagues reported that cortical and striatal neurons from the mutant mice exhibit abnormal D 1 receptor signaling and disrupted synaptic plasticity in response to D 1 receptor activation. Remarkably, these neuronal deficits could be rescued by restoring the FMR1 gene to the mutant neurons [715]. FMR1 is also suggested to be important for D 1 receptor-mediated synthesis of SAPAP3 in prefrontal cortex neurons; SAPAP3 is a post-synaptic neuronal scaffolding protein that regulates glutamate receptor trafficking and function [716].…”
Section: Reviewmentioning
confidence: 99%
“…In studies of FMR1 mutant mice, Zhuo and colleagues reported that cortical and striatal neurons from the mutant mice exhibit abnormal D 1 receptor signaling and disrupted synaptic plasticity in response to D 1 receptor activation. Remarkably, these neuronal deficits could be rescued by restoring the FMR1 gene to the mutant neurons [715]. FMR1 is also suggested to be important for D 1 receptor-mediated synthesis of SAPAP3 in prefrontal cortex neurons; SAPAP3 is a post-synaptic neuronal scaffolding protein that regulates glutamate receptor trafficking and function [716].…”
Section: Reviewmentioning
confidence: 99%
“…Later on, several other neurotransmitter receptor-mediated signal transduction pathways regulating neuronal protein synthesis have been demonstrated to be affected in FXS. Aberrant signaling in the absence of FMRP was shown to occur through (1) other Gq protein-coupled receptors such as muscarinic acetylcholine receptors (Volk et al, 2007), (2) the dopamine D 1/5 receptors (Wang et al, 2008b(Wang et al, , 2010a, and (3) tyrosine kinase receptor B (TrkB) (Osterweil et al, 2010). Of note, these signaling pathways employ similar molecular mechanisms like mGlu 1/5 -induced LTD. Activation of signaling through both Gq-coupled receptors and dopamine D1 receptors induces protein synthesis-dependent GluA receptor endocytosis (Volk et al, 2007;Wang et al, 2010a).…”
Section: Altered Signaling Of Other Membrane Receptorsmentioning
confidence: 99%
“…Although genetic and pharmacologic studies suggest that these proteins might be promising therapeutic targets, the underlying mechanisms are mostly elusive, with a few exceptions: FMRP was shown to directly regulate PI3K and PIKE mRNA translation, protein expression, and enzymatic activity (indicated by red outlines) (Gross et al, 2010;Sharma et al, 2010). Furthermore, FMRP associates with PAK and GRK2 protein, but the functional consequences of these interactions are unknown (Hayashi et al, 2007;Wang et al, 2008b). Some potential therapeutic targets show dysregulated expression (MMP-9, GABA receptors), subcellular localization (PAK and GRK2), and/or phosphorylation (ERK1/2, GSK3b, PAK, GRK2, mTOR) in the absence of FMRP (highlighted with yellow asterisks), but the detailed mechanisms are unknown and future studies will have to show whether these are the direct effects of loss of FMRP or are caused by dysregulated signaling through other pathways.…”
Section: Altered Signaling Of Other Membrane Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies utilizing pharmacological interventions that perturb the DA system, such as the psychostimulant cocaine, or potent neurotoxins, such as MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) and 6-hydroxydopamine, have found region-specific alterations in GRK2 levels (Ahmed et al, 2008a;Bezard et al, 2005;Schroeder et al, 2009). Additionally, it was found that fragile X mental retardation protein deficiency in mice causes a coincident increase in GRK2 levels in the frontal cortex and D1R hyperphosphorylation (Wang et al, 2008). Although these studies provide a potential link between GRK2 and the DA system, the physiological consequences of altered GRK2 levels to DA-dependent behaviors remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%